The Effect of Financial Literacy, Risk of Use and Benefit on Interest in Transactions Using QRIS in Generation Z - Yanti, Lutvi; Nuramelia, Alya; Ridayanti, Hilda; Rosnidah, Ida (DINASTI RESEARCH, 2025)
This quantitative research analyzes Financial literacy's impact, risks of use, and benefits of transaction interest using QRIS for Generation Z in Cirebon City. The object of this research is Generation Z in Cirebon, with a sample size of 402 people. Information was collected by conveying surveys through Google form; partial least squares (PLS) tools three analysis was used to examine the data. This research shows the results that financial literacy has a noteworthy and favorable impact on the interest variable in making transactions utilizing QRIS in Generation Z. The risk of use has a favorable and remarkable effect on the variable curiosity about transacting utilizing QRIS in Generation Z. The study's findings demonstrate that financial literacy has an influence quite a considerable favorable impact upon QRIS interest in Generation Z. The anticipated outcomes of this study will offer material regarding readers to increase their knowledge about the elements influencing interest in transacting utilizing QRIS in Generation Z. It can increase interest in transacting using QRIS.